The Effect of Group Counseling (BKP) and Self-Efficiency on Improving Students' Social Skills in Junior High School 2 Tanjung Tiram - Munir, Abdul (BIRCU, 2019)
The aim of this study is to determine the effect of group counseling (BKP) on students' social skills. Knowing the effect of self-efficacy on students' social skills. Knowing the interaction between BKP and self-efficacy towards students' social skills. This study is a quasi-experimental study with factorial 2x2 design. The subjects of this study is 8th grade student of Junior High School 2 Tanjung Tiram which amounted 43 students consisting of two class groups, where the first class as an experimental class was applied to BKP Modeling and the second class as a control class was applied to BKP Homeroom. The instrument used in this study is a questionnaire that is declared valid and reliable. Data are analyzed using two-way ANAVA analysis. From the results of the study it can be concluded that there is an effect of group counseling (BKP) on the social skills of students in Junior High School 2 Tanjung Tiram. There is a difference between BKP Modeling and BKP Homeroom in affecting students' social skills. There is no difference between low self-efficacy and high self-efficacy in affecting students' social skills. BKP Modeling is very good to use in improving students' social skills.Â